Demography of the black lion tamarin (Leontopithecus chrysopygus, Mikan) in Capão Bonito National Forest (State of São Paulo) - Caldano, Lucas Tadeu Pelagio; Monticelli, Cauê; Galetti Jr., Pedro Manoel (Neotropical Primates, 2016)
No abstract